2013
DOI: 10.2334/josnusd.55.133
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical composition of carious dentin and different layers of sound dentin

Abstract: The aim of this study was to evaluate the concentrations of calcium (Ca), inorganic phosphate (P i ) and fluoride (F) in carious dentin and in different layers of sound dentin. The samples examined were 52 permanent teeth (26 sound and 26 carious), which were subjected to two experiments to assess the mineral content of: 1) two layers (internal and external) of sound dentin and 2) sound and carious dentin. Ca and P i were analyzed using a colorimetric method with arsenazo III (C22H18As2N4O14S2) and molybdate r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 26 publications
0
5
0
1
Order By: Relevance
“…The statistical analysis revealed interaction of both factors, as the superficial dentin in the sclerotic group presented lower concentration of Ca in weight %. Previous studies have reported the mineral composition of sclerotic dentin [27][28][29][30], with lower concentration of calcium compared to sound dentin. Those results are consistent with dental caries pathology, more specific to the demineralization process, which is characterized by mineral loss [28,31,32].…”
Section: Discussionmentioning
confidence: 94%
“…The statistical analysis revealed interaction of both factors, as the superficial dentin in the sclerotic group presented lower concentration of Ca in weight %. Previous studies have reported the mineral composition of sclerotic dentin [27][28][29][30], with lower concentration of calcium compared to sound dentin. Those results are consistent with dental caries pathology, more specific to the demineralization process, which is characterized by mineral loss [28,31,32].…”
Section: Discussionmentioning
confidence: 94%
“…An attempt to overcome this limitation, however, was by the use of the adjusted grey density values which attempted to unify the grey density scale across the cases by unifying the density of subcrestal dentine. Although it is not expected that all patients truly have similar density of dentine, the density of subcrestal dentine is expected to be the tissue with the least amount of variation amongst patients because of the stability of dental structures which are not exposed to the environment (Magnus et al 2013). As such, the use of adjusted grey density values may actually increase the generalizability of the study results because the variable exposure parameters used in clinical practice are accounted for within the study.…”
Section: Discussionmentioning
confidence: 99%
“…Divergences between the chemical composition of carious and healthy teeth could also result from environmental factors (diet and pollution), the impact of other diseases, different patient ages in subsequent studies, and the use of different measurement tools. The main dentine components – calcium, inorganic phosphorous, and fluorine – play a key role in tooth demineralisation and remineralisation [ 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%